The quiz book for spies - Becker, Helaine (Toronto ; New York : Scholastic Canada, 2012)
Presents a series of quizzes to determine one's ability to be a spy.
5.8
3-6
3-6
Keywords: Espionage -- Miscellanea -- Juvenile literature; Spies -- Miscellanea -- Juvenile literature; Espionage -- Miscellanea; Spies -- Miscellanea; Espionage -- Miscellanea; Spies -- Miscellanea